Diamond biocompatible coatings for medical implants - Starikov, V. V.; Starikova, S. L.; Mamalis, A. G.; Lavrynenko, S. N. (Collegium Basilea & AMSI, 2016)
New carbon (diamond-like) nanocomposite coatings deposited from a C60 ionic beam can be used as a wear-resistant protective coating for implants. It was found that these coatings enhance resistance to тelectrochemical corrosion processes due to a shift of the material’s electrode potential to a zone of positive values. They also promote a complex of reparative, adaptative and compensatory reorganization that accelerates the healing processes in the vicinity of the implant.
Keywords: biocompatibility; diamond-like films; electrode potential; implant coating; nanocomposite; structure